Agriculture in Mediterranean Europe between old and new paradigms - Ortiz-Miranda, Dionisio; Moragues-Faus, Ana; Arnalte Alegre, Eladio (Research in rural sociology and development ;, 2013)
Mediterranean agriculture is by and large envisaged as a landscape of small farms of high nature value producing worldwide recognisable quality food products that make up the basis of the famous Mediterranean diet and shape Southern European cultures. However, the dynamics developing in the Mediterranean countryside are further complex and diverse; comprising differentiated agricultural systems which have been scarcely analysed in an integrated fashion. This volume illustrates and deepens the understanding of current agrarian dynamics developing in Mediterranean countries in the light of recent theoretical contributions. The book compiles and analyses a set of Mediterranean case studies that show the range of transformations shaping contemporary agriculture in Southern Europe, which allow considering the usefulness of recent theoretical frameworks in explaining the array of dynamics underway; contributing to the refinement of contemporary conceptualizations.